RANCANG BANGUN SISTEM INFORMASI BERBASIS WEB PADA KB TK IT YAPEMRI BSD - Diandra Aurelliea Azra (2023)
Today, technology is growing rapidly and has become a part of everyone's life. Often technology is applied in the workplace or at school, such as the use of information systems. However, not all institutions implement information systems properly. For example, in the education sector, information systems are not widely used for Playgroups and Kindergartens. Knowing the importance of information systems, KB TK IT Yapemri BSD wanted a website-based information system. KB TK IT Yapemri BSD is a newly established institution, so it doesn't have an information system in the form of a website before. The purpose of this study is to design a facility for KB IT Yapemri BSD Kindergarten in conveying information to parents and the community and managing academic data. There are four main features, namely registration features, learning features, graduation features, and payment features. In establishing this information system, the PIECES analysis method was used to identify problems, and the Scrum method to design the system. This research produced a website-based information system to facilitate the processing and storage of information at KB TK IT Yapemri BSD.